Agriculture & Food Systems to 2050 - Global Trends, Challenges and Opportunities - Serraj, R.; Pingali, Prabhu L. (World Scientific Publishing, 2018)
This book features a comprehensive foresight assessment, exploring the pressures — threats as well as opportunities — on the global agriculture & food systems between now and 2050. The overarching aim is to help readers understand the context, by analyzing global trends and anticipating change for better planning and constructing pathways from the present to the future by focusing on the right questions and problems. The book contextualizes the role of international agricultural research in addressing the complex challenges posed by UN 2030 Agenda and beyond, and identifies the decisions that scientific leaders, donors and policy makers need to take today, and in the years ahead, to ensure that a global population rising to nine billion or more combined with rising incomes and changing diets can be fed sustainably and equitably, in the face of the growing climate threats.